Inteligencia emocional y la resolución de conflictos en los adolescentes de la Unidad Educativa Francisco Huerta Rendon de la ciudad de Babahoyo - Asencio Martinez, Britanny Nayelly (2025)
The objective of this research is to describe how emotional intelligence is related to conflict resolution in adolescents of the “Francisco Huerta Rendón” Educational Unit in the city of Babahoyo. Emotional intelligence is the ability to recognize and express emotions in human beings, which facilitates thinking and regulates emotions. On the other hand, conflict resolution is the negative interpretation of conflictive contexts, which emphasizes the search for solutions, observing and converting the negative into a positive and constructive way. The study has a population of 240 adolescent students between 14 and 16 years old, in which a sample of 86 young people from higher basic education was chosen, using non-probabilistic convenience sampling. The research is descriptive, a mixed approach and a non-experimental cross-sectional research design were used. Data collection was also carried out through two psychometric tests, the Bar-On's Emotional Intelligence Inventory for Adolescents (EQ-i: YV), which aims to assess and measure emotional intelligence, created by Reuven Bar-On (1997). And the Thomas-Kilmann Conflict Mode Instrument (TKI), the objective of this tool is to evaluate and help to understand conflict management, the instrument was designed by Kenneth W. Thomas and Ralph H. Kilmann in (1974). An interview with teachers was also conducted in order to learn more about the variables within the classroom. The results of the research show that in the inventory (EQ-i: YV), there is a total of 85% of students with low emotional intelligence, while 13% show medium emotional intelligence and finally 2% of adolescents show high emotional intelligence. The TKI instrument reveals that the avoidance component is the highest with 32%, followed by the competitive component with 22%, 20% of adolescents show complacency, followed by the collaborative component with 17%, and finally, the lowest component with 9% is commitment. With respect to the interview applied it is evident that teachers help to identify and express emotions to students through different methods and strategies, so they have a structure to deal with conflicts, also teachers serve as mediators in such cases to promote empathy among young people.